Factors Influencing Technical Efficiency in Cashew Nut Production - R.K, Koech; P.M, Nyangweso; S.M, Mwakubo (IJRDO - Journal of Business Management, 2016)
The agricultural sector is an important pillar of the coastal economy. Cashew nuts production iswidely practiced in Kilifi County. Cashew farming faces several challenges among them pestsand diseases. Given a set of inputs, an economic agent will either be efficient or inefficient.There are several factors, both internal and external that may determine the level of operation bya farmer. To determine the factors influencing the technical efficiency level of a farmer a twostagestochastic frontier analysis was done. The first stage generated efficiency scores for eachfamer which were then regressed against famers characteristics in the second stage. The resultsof the second stage regression are presented in this paper. The size of the household, gender andavailability of extension services were found to positively influence the technical efficiency of afarmer. Gender sensitive policies should therefore be formulated and implemented as a way ofassisting farmers attain higher level of efficiency. Intensification of extension service will alsosee an improvement in farmers’ level of efficiency.